Pendampingan Pembuatan Website untuk Sistem Informasi di Panti Asuhan Budi Mulya - Harlina, Tintin; Irawan, Nur Hadi (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
This service aims to develop an orphanage website for Field Work Practice (PKL) activities. This form of community service between students and lecturers has the impact of making it easier to process administrative data and information in orphanages. The method used to carry out community service activities uses Agile Software Development and socialization or training. The results of community service show that the website created is feasible and can be used for information and promotion systems at the Budi Mulya orphanage. So it can be concluded that the website created is suitable for use in processing data, helping convey information and promotions about the Budi Mulya orphanage, which was previously done manually.